(untitled) (Journal of Medical Sciences, 2021)
Many bacterial species can produce biofilm on medical device surfaces. Biofilm formation increases the persistence of infection and antimicrobial agents’ resistance as well as a healthcare-associated infection. The urinary catheter is one of the medical devices that pathogenic bacterial species can colonies and form biofilm on their surfaces leading to recurrent and persistent urinary tract infections. This study aimed to detect biofilm formation of different gram-positive and gram-negative bacterial species isolated from rubber and silicone urinary catheters. Evaluation of biofilm formation was performed by using 0.1% of crystal violet and pieces of 1 cm long of rubber and silicone catheters. After washing catheter pieces three times with phosphate buffer saline finally washed with ethanol. The optic density of alcohol wash was measured at 450nm. Biofilm production was evaluated according to the mean of OD as following: 0.120; weak biofilm-forming, 0.120-0.240 moderate biofilm-forming, and 0.240 strong biofilm forming. The results of this study reported 62.3% of tested isolates were strong biofilm producers. Gram-negative bacteria were more potent in biofilm formation than gram-positive bacteria (78.9% and 32.7% respectively). The highest species strongly formed biofilm in gram-positive was E. faecalis in rubber urinary catheter while Staph. epidermidis was the highest in silicon urinary catheters. Most gram-negative species were strong biofilm producers. The high prevalence of biofilm-forming bacterial species among collected isolates is considered a risk factor that might lead to recurrent or persistent urinary tract infection and healthcare-associated infection.